Analysis of Production Cost Calculations Using The Full Costing Method of Mantahukan Fish on Ud. Kerupuk Ikan Kembar - Tina, Agustina Mulyani (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya (UPR), 2023)
Abstract : This research was conducted at UD Kerupuk Ikan Kembar which operates in the Mantahukan fish cracker product industry, with the aim of knowing the calculation of the cost of production at UD Kerupuk Ikan Kembar and to analyze the application of the full costing method for calculating the cost of production at UD Kerupuk Ikan Kembar. This type of research uses quantitative descriptive research. Data was collected using documentation, interviews, and data analysis methods in the form of descriptive analysis. The research results show that UD Kerupuk Ikan Kembar still uses a simple production cost calculation method by adding up production costs consisting of raw material costs, direct labor costs, and supporting costs. Application of the full costing method by detailing all production costs that occur, including raw material costs.